1995
DOI: 10.1210/mend.9.2.7776971
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of ligand-dependent androgen receptor stabilization: receptor domain interactions influence ligand dissociation and receptor stability.

Abstract: The molecular basis for the different physiological effects of testosterone (T) and dihydrotestosterone (DHT) was investigated using recombinantly expressed wild-type and mutant androgen receptor (AR). Rates of androgen dissociation from nuclear and cytoplasmic AR were compared with hormone- and concentration-dependent receptor degradation rates. T dissociates from AR 3 times faster than DHT or methyltrienolone (R1881) and is less effective in stabilizing the receptor. Analysis of AR deletion mutants and AR/gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(50 citation statements)
references
References 4 publications
8
42
0
Order By: Relevance
“…In the control transfection with scramble siRNA (ARc), R1881 increased levels of AR protein ( Figure 4a). This was consistent with ligand stabilizing the AR protein to increase levels as previously reported (Kemppainen et al, 1992;Zhou et al, 1995). FSK did not significantly alter the levels of AR protein (P ¼ 0.091).…”
Section: A Genome-wide View Of Androgen and Fsk Effectssupporting
confidence: 92%
“…In the control transfection with scramble siRNA (ARc), R1881 increased levels of AR protein ( Figure 4a). This was consistent with ligand stabilizing the AR protein to increase levels as previously reported (Kemppainen et al, 1992;Zhou et al, 1995). FSK did not significantly alter the levels of AR protein (P ¼ 0.091).…”
Section: A Genome-wide View Of Androgen and Fsk Effectssupporting
confidence: 92%
“…Although Cdk1 inhibitors could suppress both Ser-81 phosphorylation and AR transcriptional activity, previous transfection studies in AR-negative cell lines have shown that Ser-81 is not required for AR transcriptional activity (13,35). We similarly found that transfected ARs and an S81A mutant had comparable levels of androgen-stimulated transcriptional activity in HeLa cells, as assessed on an ARE 4 -luciferase reporter gene (Fig.…”
Section: Cdk1supporting
confidence: 60%
“…It is well recognized that androgens can enhance AR protein levels by increasing the half-life, as well as by stimulating the phosphorylation Zhou et al, 1995;Kemppainen et al, 1992;Krongrad et al, 1991) of the AR. It has been shown that agonistbound AR is more resistant to in vitro proteolytic digestion than an unbound AR, indicating a conformational change of the AR induced by androgens.…”
Section: Discussionmentioning
confidence: 99%